Quality of Life in Patients with Pickwickian Syndrome (Obesity Hypoventilation Syndrome): A Systematic Literature Review - William Giovanni Mulyanaga; Dian Marta Sari; Farida Arisanti (Rifa'Institute, 2026)
Introduction: Pickwickian Syndrome, also known as Obesity Hypoventilation Syndrome, is a chronic respiratory disorder associated with obesity that substantially affects patients’ physical, psychological, and social quality of life. Although several treatment approaches are available, their effects on quality-of-life outcomes have not been comprehensively synthesized. Objective: This study aimed to evaluate the influence of different treatment approaches on the quality of life of patients with Pickwickian Syndrome. Method: A systematic literature review was conducted using PubMed, EBSCOhost, and Web of Science databases. A total of 28 articles were identified and screened according to predefined eligibility criteria based on the Population, Intervention, Comparison, and Outcome framework. Following duplicate removal and full-text assessment, six studies were included in the final review. Result and Discussion: The findings showed that weight-loss interventions, including bariatric surgery and dietary management, improved body weight, sleep-disordered breathing, and quality of life. Rehabilitation programs combining exercise, nutritional counseling, and behavioral support enhanced functional capacity, exercise tolerance, and health-related quality of life. Positive airway pressure therapies, including continuous positive airway pressure and noninvasive ventilation, improved gas exchange, sleep quality, daytime alertness, respiratory symptoms, and overall well-being. Conclusions: Different treatment approaches positively affect the quality of life of patients with Pickwickian Syndrome. Weight-loss interventions target the underlying cause of the disease, rehabilitation programs improve functional and psychosocial outcomes, and positive airway pressure therapies effectively alleviate respiratory and sleep-related symptoms